2022
DOI: 10.1038/s41467-022-34910-5
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Spike triggers barrier dysfunction and vascular leak via integrins and TGF-β signaling

Abstract: Severe COVID-19 is associated with epithelial and endothelial barrier dysfunction within the lung as well as in distal organs. While it is appreciated that an exaggerated inflammatory response is associated with barrier dysfunction, the triggers of vascular leak are unclear. Here, we report that cell-intrinsic interactions between the Spike (S) glycoprotein of SARS-CoV-2 and epithelial/endothelial cells are sufficient to induce barrier dysfunction in vitro and vascular leak in vivo, independently of viral repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
36
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 90 publications
2
36
1
Order By: Relevance
“…Finally, as LG3 exists as either a part of perlecan found primarily within vascular basement membranes or as a proteolytically cleaved protein in circulation (Parker et al, 2012) which exerts considerable effect on blood vessel growth through both pro‐ and anti‐angiogenic mechanisms (Biose et al, 2022; Clarke et al, 2012; Lee et al, 2011; Segev et al, 2004), our results suggest that LG3 may play a role in SARS‐CoV‐2 vascular barrier disruption as observed by others (Biering et al, 2022). This may explain, in part, the predominant vasculopathy of COVID‐19 pathogenesis (Flaumenhaft et al, 2022), which we hypothesize that perlecan LG3 may play and previously unrecognized but significant role.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Finally, as LG3 exists as either a part of perlecan found primarily within vascular basement membranes or as a proteolytically cleaved protein in circulation (Parker et al, 2012) which exerts considerable effect on blood vessel growth through both pro‐ and anti‐angiogenic mechanisms (Biose et al, 2022; Clarke et al, 2012; Lee et al, 2011; Segev et al, 2004), our results suggest that LG3 may play a role in SARS‐CoV‐2 vascular barrier disruption as observed by others (Biering et al, 2022). This may explain, in part, the predominant vasculopathy of COVID‐19 pathogenesis (Flaumenhaft et al, 2022), which we hypothesize that perlecan LG3 may play and previously unrecognized but significant role.…”
Section: Discussionsupporting
confidence: 81%
“…While it is known that SARS‐CoV‐2 enters host cells via binding ACE2 (Hoffmann et al, 2020; Lan et al, 2020; Letko et al, 2020; Tian et al, 2020; Walls et al, 2020), other cell surfaces and nearby biomolecules such as ECM proteins have also shown a binding affinity for the SARS‐CoV‐2 spike protein RBD, although the extent to which these molecules modulate infectivity is still unclear (De Pasquale et al, 2021; Huang et al, 2022; Jayaprakash & Surolia, 2021; Lo et al., 2022; Mehdipour & Hummer, 2021; Nguyen et al, 2021; Yu et al, 2020). As recent studies have suggested that negatively charged heparan sulfate proteoglycans may act as a cofactor for SARS‐CoV‐2 binding to ACE2 known to have significant effects on vascular function and vascular barriers (Biering et al, 2022; Hashimoto et al, 2022; Martínez‐Salazar et al, 2022), we sought to characterize this interaction with the c‐terminal LG3 subdomain of perlecan domain V. To date, no conclusive studies have been conducted investigating the potential role that perlecan LG3 may have in SARS‐CoV‐2 pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Both SARS-CoV and SARS-CoV-2 have developed an efficient mechanism to evade the immune response of infected individuals by inducing expression of the immunosuppressive cytokine TGF-β in infected cells. They use several mechanisms to induce expression of TGF-β and signal transduction in infected cells, such as integrin-mediated induction by the spike protein [19], nucleocapsid protein pairing with Smad3 [20,21], induction of TGF-β target genes (including TGF-β itself) [6], and induction by orf3 and orf8 encoded proteins [22].…”
Section: Discussionmentioning
confidence: 99%
“…Early TGF-β expression has severe pathogenic consequences, inhibiting the killing of infected cells by NK cells [6] and redirecting the immune response in severely affected patients toward a chronic autoimmune response [20,32]. It may also impact fibrinogenesis [22], vascular leakage [19], and thrombosis in COVID-19 [26]. Therefore, detection of TGF-β levels at an early stage after the onset of symptoms (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…4 Inflammation triggers endothelial hyperpermeability, vascular leak, disorder in exchanges between blood and tissues, which eventually lead to lung edema and respiratory failure. 5 The development of novel therapeutics, to support barrier function, is crucial for those hospitalized patients in need. 6 Growth hormone-releasing hormone antagonists (GHRHAnt), which were initially developed to treat cancers, may represent an exciting new possibility to treat ARDS.…”
mentioning
confidence: 99%